Quality of life in rural and urban patients with Parkinson’s disease - Valeikienė, Vaineta; Juozulynas, Algirdas; Savičiūtė, Rasa; Venalis, Algirdas; Jurgelėnas, Antanas (Acta medica Lituanica, 2013)
Parkinson’s disease (PD) belongs to a group of neurodegenerative diseases. PD diagnosis is clinical, based on these signs: tremor, rigidity, bradykinesis, akinesis or hypokinesis. In the case of patients with chronic illnesses and impaired mobility function, impact on QOL and QOL considerations are of special importance for the consequences in everyday life. Aim of the work was to determine and compare the quality of life in rural and urban patients with Parkinson’s disease. Respondents were randomly selected from the register of community-based health maintenance organizations. PD patients were identified as having clinical diagnosis of Parkinson’s disease. Persons who satisfied the following criteria were eligible to participate in this study: • Parkinson’s disease or Parkinson’s syndrome was diagnosed from 1 January 1978 to 1 January 2009. • Patients with PD were alive until 1 January 2009. • The diagnosis of PD or Parkinson’s syndrome and treatment with antiparkinsonic medicines were marked in the ambulatoric history of the patients. Results. Quality of life in patients with Parkinson’s disease is determined by motor, mental and emotional disorders. It impedes daily routine, sometimes makes a person totally disabled, effects interpersonal relationships, increases risk of self-inflicted wound. Patient’s self-sufficiency decreases as illness makes progress and the patient becomes more dependent on other people and the quality of life is decreasing. Conclusions. Parkinson’s patients often feel pain. Both rural and urban people feel negative feelings that are hard to fight. All studied patients with dominative rigidity and slow movements had poor ability to move from the beginning of this disease. Tremor did not disabled patients so severely: patients with tremor could move easier.